Improving Understanding of Mathematical Concepts With Multilevel Simulation Learning Models in Elementary School Students - Desi Susanti (Jurnal Pendidikan Profesi Guru, 2023)
Student learning outcomes in Mathematics class are still low. The average grade for class V is still below the ideal completeness standard of 75% set by SDN 06 Parit Lintang, Salatiga District, Sambas Regency. This is because when teaching, the teacher only gives material while students pay attention, take notes, and do practice questions. Based on the problems raised, the purpose of this study is to change fractions to percents and vice versa through a multilevel simulation method. This exploration is a homeroom research activity, with a total of 23 students consisting of 12 female students and 11 male students. The inspection strategy carried out includes compiling, carrying out activities, paying attention and contemplating cycles. Learning outcomes on the main pattern of delegating subject authority are not good. From the ideal culmination score of 75%, the new old style fulfillment score reaches 44%. Cycle II reached 78%. Thus, the use of the staggered reproduction model can improve the understanding of numerical ideas in 5th grade elementary school.